Psychosocial Needs of Internally Displaced Persons: A focus on Women and Children - Julie, Akpotor (International Journal of Psychosocial Rehabilitation, 2020)
The predicament of internally displaced persons in Nigeria has attracted much attention at the national and international levels, and academia is not left out. The study was carried out with the explanation of vital secondary sources, especially books, journals, newspapers, and internet sources. Through these sources, the paper examined the psychosocial needs of internally displaced persons (IDPs), focusing on women and children. The psychosocial needs are the interactions of an individual’s emotional and mental wellbeing and the ability to function satisfactorily in the social environment. In contrast, therefore, individuals will experience psychosocial mobility when there is an absence of or insufficient assessment of psychosocial needs. The paper has therefore revealed that this is the plight of most IDPs who have been displaced from their homes as a result of spreading communal conflicts, insurgency, or natural disasters. In their suffering, distress, and confused state, their well-being will continue to be jeopardized if something is not done urgently. Against this backdrop, some basic recommendations have been suggested. It was therefore recommended that a comprehensive humanitarian action be coordinated to provide women and children in IDP camps with welfare materials, health and educational facilities, vocational training and tools of the trade, empowerment programs, and security that will facilitate their psychosocial satisfaction. The government, international donors and non-governmental organizations should gear their efforts in this direction